Cytotoxicity screen of the acyclic nucleoside phosphonates against bloodstream stage of Trypanosoma brucei and validation of their putative target hypoxanthine/xanthine/guanine phosphoribosyltransferase - Mittermayr, Martina (Jihočeská univerzita, 2012)
The aim of this study was to test several compounds of acyclic nucleoside phosphonates (ANPs), which are thought to inhibit the purine salvage pathway enzyme hypoxanthine/xanthine/guanine phosphoribosyltransferase (HGXPRT) of the bloodstream stage of Trypanosoma brucei. Further we intended to elucidate if HGXPRT enzymes are essential for the survival of the bloodstream T.brucei.
Cytotoxicity screen of the acyclic nucleoside phosphonates against bloodstream stage of Trypanosoma brucei and validation of their putative target hypoxanthine/xanthine/guanine phosphoribosyltransferase
Keywords: Trypanosoma brucei; HAT; Human African Trypanosomiasis; RNAi; HGXPRT; acyclic nucleoside phosphonates; ANP; purine salvage pathway; AlamarBlue; bloodstream T.brucei; Trypanosoma brucei; HAT; Human African Trypanosomiasis; RNAi; HGXPRT; acyclic nucleoside phosphonates; ANP; purine salvage pathway; AlamarBlue; bloodstream T.brucei